The New Economics of Regulation Ten Years After - Laffont, Jean-Jacques (Econometrica, 1994)
The new economics of regulation is an application of the principal-agent methodology to the contractual relationship between regulators and regulated firms. After a critique of the traditional paradigms of regulation from the point of view of information economics a canonical model of regulation under asymmetric information is developed. A survey of the main results obtained in the new economics of regulation is then provided, in particular concerning the implementation of optimal contracts by a menu of linear contracts, the dichotomy between pricing and cost reimbursement rules, the auctioning of incentive contracts, the dynamics of contracting under limited commitment, and the hierarchical problems in regulation. Empirical implications are then discussed and avenues of further research are described in the conclusion.